Enigmatic morphological disparity in tarsometatarsi of giant penguins from the Eocene of Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia (2011)
The only record of the Paleogene Antarctic Sphenisciformes comes from the Eocene La Meseta Formation (Seymour Island, Antarctic Peninsula). The analysis of tarsometatarsi attributed to the genus Anthropornis ("giant" penguins) from the Argentine, Polish and Swedish collections revealed an intriguing heterogeneity within these taxonomically important elements of the skeleton. The unique hypotarsal morphology challenges the current systematics of large-bodied penguins and sheds new light on their evolution.